IMPLEMENTATION OF RELIGIOUS MODERATION ATTITUDE THROUGH ISLAMIC RELIGIOUS EDUCATION FOR CULTURAL COMMUNITIES - Syatria Adymas Pranajaya; Adriansyah. NZ; Musrizal; Muhammad Fuadi (Adisam Publisher, 2024)
Religious moderation is important for the next generation to advance the nation in the future, the cultivation of moderate Islamic values needs to be pursued as an effort to prevent exposure to radicalism. A concrete step in providing the values of religious moderation to the younger generation is through religious education. Islamic Religious Education is in a vortex of diversity, plurality with an educational paradigm that is multicultural, multidimensional and does not exist in a vacuum, so this suggests that individual educational stakeholders, educational actors, objects, and beneficiaries of educational results must be able to learn together with other individuals in an atmosphere mutual respect, mutual tolerance and mutual understanding, as part of self-development or transformation, educational institutions, strategies, models or even learning process techniques. In the life of a multicultural society, there is bound to be plurality which, if not addressed wisely, will create the threat of conflict, whether from religious, cultural or ethnic aspects. With that, there needs to be awareness and understanding of religious moderation in order to create social peace and security that is maintained and understood contextually in various aspects of diversity.